Dietary factors associated with metabolic syndrome and its components in overweight and obese Brazilian schoolchildren: a cross-sectional study - Madalena Rinaldi, Ana Elisa; Costa Pinto Gabriel, Gleice Fernanda; Moreto, Fernando; Corrente, Jose Eduardo; Portero McLellan, Katia Cristina; Burini, Roberto Carlos [UNESP] (Biomed Central Ltd, 2016)
Background: The metabolic syndrome (MS) has been assessed since childhood mainly because of the nutritional and epidemiological transition that has occurred worldwide. Our objectives were to explore the MS and its components according to anthropometric and demographic factors and to assess the relationship among MS components and dietary characteristics in overweight and obese schoolchildren. Methods: This was a cross-sectional study which included 147 schoolchildren (aged 6-10 years) from three elementary schools, with body mass index (BMI) higher than the 85th percentile. Sexual maturation stages, anthropometric measures (weight, height, skinfold thickness and waist circumference), biochemical data (glucose, HDL-C and triacylglycerol), blood pressure and dietary intake were assessed. The metabolic syndrome was diagnosed if three or more of the following components were presented: waist circumference >= 90th age and sex-specific cut-off, blood pressure >= 90th age, sex and height-specific cut-off, glucose >= 100 mg/dL, HDL-C >= 40 mg/dL and triacylglycerols >= 110 mg/dL. The dietary intake was assessed by three non-consecutive 24-h recalls. The T test, Kruskal-Wallis and multiple linear regression analysis were applied to assess MS components and dietary intake. Results: The MS percentage was 10.2 % and it was higher in obese children and ones with high body fat percentage. The waist circumference was the main altered component of MS and 62 % of overweight schoolchildren showed at least one altered component of MS. The components of metabolic syndrome associated with dietary intake were triacylglycerol (positive association with saturated and monounsaturated fat, whole-milk products and processed foods and negative associated with legumes and polyunsaturated fat), glycemia (positive association with processed foods and negative with cereals), HDL-C (positive association with vegetables and greens) and waist circumference was negative associated with protein. Conclusions: The frequency of MS was higher in obese than overweight schoolchildren and the frequency of at least one MS component was high in more than half of our subjects. The waist circumference was the most frequent among all other components. The triacylglycerol and glycemia were the most frequent MS components associated with dietary intake. Unprocessed food was considered a protective dietary factor for MS metabolic components and processed food with high percentage of sugar and saturated fat was a risk factor for MS metabolic components.
Keywords: Metabolic syndrome; Schoolchildren; Dietary intake; Overweight; Obese